(untitled) (World Science, 2019)
Tibial fractures are very common injuries that require surgical management. For many cases, when the fracture involves the joint further complications occur, such as joint stiffness, osteoarthritis, aseptic necrosis of articular surfaces, ankylosis, infection complications, etc. To prevent joint stiffness open reduction and internal fracture fixation is used. That allows better positioning of fracture fragments forming joint surface and improve outcome. The article analyses results of surgical treatment of intraarticular fractures as well as biomechanical factors that are affecting the joint within the healing process and in later outcome period. Various treatment procedures are suggested to prevent development of osteoarthritis or to decrease its severity. The following options are used on all stages of treatment starting since the moment of injury, primary surgical procedures, rehabilitation period, and further non-surgical treatment in the internal medicine department. Important roles are assigned for use of chondroprotective drugs, intraarticular injections of Hyaluronic acid, physiotherapy and physical activity.